The role of bank automated services in gaining customers' trust: a practical study in UAE - Mohammad A Al-Hawari. (Penerbit Universiti Kebangsaan Malaysia, 2011)
The main purpose of this paper is to highlight the significance of automated services factors on customer trust within United Arab of Emirates (UAE) banking contexts. The paper proposes a conceptual model of the relationship between automated factors and customers trust. Survey was designed and data collected through mall intercept method. AMOS 6 was used to test for the hypothesized relationships. Most of automated factors have direct relationship with customer trust. Queue management and convenience were the only factors that did not have any relationship with the dependent variable customer trust. The proposed model has the potential to help UAE banks' managers to strengthen the customerbank relationship and, ultimately, to enhance customer trust especially at the light of the credit crunch the most banks in UAE are facing.